Post-harvest treatment of papaya (carica papaya L.) - Ammy, Anak Stephen Nanyi. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Post-harvest treatment of cv.Exotica and cv. One foot papaya was carried out. The fruits were subjected to three treatments ie: dipping in hot water bath at 48°C for 20 minutes and stored at lo°C, dipping in hot water bath at 60°C for I minute and stored at 10°C and stored at ambient without any treatment. The fruit colour was observed and recorded from day 0 until 21. It was found that cv. Exotica and cv. One foot papaya can be kept for up to 21 days when treated with hot water at 48°C for 20 minutes and at 60°C for 1 minute. For control, cv.Exotica papaya can be kept for not more than 7 days meanwhile cv. One foot papaya can last for not more than 6 days. Samples were analyzed for quality parameter such as acidity, total soluble solids, vitamin C, pH and Brix after every two days interval ie: day 2,4,6,8, 10, 12, 14, 16, 18 and 20. Statistical analysis showed that there were no changes quality parameters for both varieties during storage and due to different treatment temperature. However, there were changes in some quality parameters due to different treatment temperature and during storage. Analysis result showed that postharvest treatment of papaya can last for up to 20 days or longer when treated at 48°C and 60°C for 20 minutes and 1 minute respectively. The ambient samples could only be kept for not more than 7 days for cV.Exotica papaya and not more than 6 days for cv. One foot papaya.